Eggshell waste as a promising adsorbent for phosphorus recovery from wastewater: A review - Protima Sarker; Xin Liu; Md Shiblur Rahaman; Masahiro Maruo (Water Biology and Security)
Phosphorus is a plant nutrient that is the main driving force of eutrophication, a serious type of water pollution. Various techniques and materials have been used to identify cost-effective, environmentally friendly options for phosphate removal. Eggshell waste is a good natural source of calcium, which is an effective adsorbent for phosphate removal. Many studies have examined pure eggshell, eggshell chemically modified with metal salts, and calcined eggshell mixed with biochar for phosphate removal. Here, most research on eggshell-based phosphate removal is reviewed to clarify the effectiveness of different types of modifications. Adsorption isotherm and kinetics models are the best methods for identifying the mechanism of adsorption, and both pure and modified eggshell have been characterized to understand the morphological and structural changes after adsorption. Furthermore, the phosphate-loaded material could be used as a fertilizer if it is not modified with harmful or toxic material. Eggshell-based adsorbents may provide cheaper, ecofriendly adsorbents for phosphate removal.